Coping mechanisms of photo film developing business towards technology innovations in Iloilo City - Baraquia, Rey Adrian; Bolivar, Krystelle; Orendain, Manuela Joy; Piamonte, Arvy Corazon; Piansay, Ravie; Rivera, Angelo
The research aims to know the actions and responses of photo-film developing business with new technologies and inventions in photography. The research has the following objectives: (1) assess the marketing aspect of photo-film developing businesses and determine the marketing efforts done to deal with technology change; (2) determine the innovations that photo-film developing businesses use to cope with technological advancement and (3) determine the firm's disposal methods and alternative uses of obsolete equipments. The research also has the following hypotheses: (1) the marketing aspect of the business does not affect coping mechanism; (2) technological innovations do not influence coping mechanism and (3) disposal methods and alternative uses of obsolete equipments do not affect coping mechanism. The research has seven (7) respondents and because of its size, the research included case studies to support the findings. It is found out that the marketing strategy and the product and services innovations affect the coping mechanism however the alternative plan and disposal of equipment and facilities does not. The null hypotheses: (1) the marketing aspect of the business does not affect coping mechanism; (2) technological innovations do not influence coping mechanism were all rejected and the null hypothesis that states: disposal methods and alternative uses of obsolete equipments do not affect coping mechanism was accepted.